2019
DOI: 10.3390/pr7120936
|View full text |Cite
|
Sign up to set email alerts
|

CFD Study of Gas Holdup and Frictional Pressure Drop of Vertical Riser Inside IC Reactor

Abstract: The internal circulation system in Internal Circulation (IC) reactor plays an important role in increasing volumetric loading rate and promoting the mixing between sludge and wastewater. In order to design the internal circulation system, the flow behaviors of gas-liquid inside vertical riser should be studied in detail. In the present study, the Multiple Flow Regimes model is adopted to capture the phase interface for different flow conditions. The flow patterns, internal circulation flow rate, gas holdup, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…From the numerical point of view, the interface between water and air at steady state of each simulation does not appear sharp due to the intrinsic limit of the Eulerian–Eulerian model like the volume of fluid employed to simulate the two-phase flow. As Wang et al 43 found out, to make the numerical results comparable to the experimental ones when using a Eulerian–Eulerian model, it is mandatory to set a specific value for the air volume fraction to identify the interface position. Before addressing the gassed condition, the average liquid phase level in steady-state conditions was evaluated as a spatial average using six planes passing through the central axis of the fermenter.…”
Section: Methodsmentioning
confidence: 99%
“…From the numerical point of view, the interface between water and air at steady state of each simulation does not appear sharp due to the intrinsic limit of the Eulerian–Eulerian model like the volume of fluid employed to simulate the two-phase flow. As Wang et al 43 found out, to make the numerical results comparable to the experimental ones when using a Eulerian–Eulerian model, it is mandatory to set a specific value for the air volume fraction to identify the interface position. Before addressing the gassed condition, the average liquid phase level in steady-state conditions was evaluated as a spatial average using six planes passing through the central axis of the fermenter.…”
Section: Methodsmentioning
confidence: 99%
“…The Special Issue showcases ten full-length original research articles [13][14][15][16][17][18][19][20][21][22], one short communication [23], and one review article [24] covering different aspects of various processes for bioenergy and resource recovery from biowaste. Specifically, the accepted manuscripts covered a range of essential topics in the areas of anaerobic digestion, microbial fermentation, and thermochemical conversion targeting various value-added resources, including biogas, syngas, bio-oil, and organic acids ( Figure 1).…”
Section: Statistics Of the Special Issuementioning
confidence: 99%
“…Dong et al [19] presented a Computational Fluid Dynamics (CFD) simulation on hydrodynamic characteristics of anaerobic granule swarms with various voidages in an internal circulation (IC) anaerobic reactor. Moreover, Wang et al [18] presented another CFD study on the understanding of flow behaviors of gas-liquid inside the vertical riser inside the IC anaerobic reactor. These simulation results would be useful in the optimization of the design and operation of IC anaerobic bioreactors.…”
Section: Overview Of the Contributionsmentioning
confidence: 99%